A High-throughput routing metric for multi-hop Underwater Acoustic Networks. (May 2015) - Azad, Saiful; Hasan, Khandaker Tabin; Nandi, Dip; Pathan, Al-Sakib Khan
Graphical abstract: Highlights: We investigate performance of various topology-based routing metrics in Underwater Acoustic Network. Acquired knowledge is applied to design a new routing metric, Cubic Min to Avg Signal-to-Noise Ratio (CMAS). This metric is capable of selecting high-throughput links. Simulation results demonstrate the efficiency of the proposed metric. Abstract: In most wireless network architectures, a routing metric plays an important role for a routing protocol to select suitable paths (or, links) for communications. An inefficient routing metric may increase overall transmission cost per packet by selecting lossy links and thereby may lead to poor throughput. Underwater Acoustic Networks (UANs), where most of the nodes operate on battery power, prefer topology-based routing metrics over active probing based routing metrics. Considering this fact, in this paper, we investigate the performance of various topology-based routing metrics over UAN-architecture. We then apply the acquired knowledge to design a new routing metric called Cubic Min to Avg Signal-to-Noise Ratio (CMAS), which is capable of selecting high-throughput links. We evaluate the performance of the proposed metric with other available topology-based routing metrics in underwater scenario. Simulation results demonstrate that the proposed metric attains significantly higher throughput than that of the other compared metrics.